Phytochemical analysis, identification of bioactive compounds using GC-MS, in vitro and in silico hypoglycemic potential, in vitro antioxidant potential, and in silico ADME analysis of Chlorophytum comosum root and leaf - Kavya, P.; Theijeswini, R. C.; Gayathri, M. (Frontiers in Chemistry, 2024)
Chlorophytum comosum is a plant with medicinal potential traditionally used to treat different diseases. The present study aimed to determine the bioactive compounds, hypoglycemic and antioxidant potential of C. comosum root and leaf in vitro and in silico. The ethyl acetate extracts of C. comosum root and leaf were analyzed by GC-MS to determine the bioactive compounds present. The hypoglycemic potential of the extracts was evaluated by α-amylase, and α-glucosidase, glucose diffusion inhibitory assays, and glucose adsorption assayin vitro. The ethyl acetate extract of C. comosum root inhibited α-amylase, and α-glucosidase, enzymes and glucose diffusion in a concentration-dependent manner with IC50 values of 205.39 ±0.15, and 179.34±0.3 and 535.248 µg/ml, respectively, and the ethyl acetate extract of C. comosum leaf extract inhibited α-amylase and α-glucosidase enzymes with IC50 values of 547.99±0.09, and 198.18±0.25 µg/ml respectively. C. comosum root and leaf extracts also improved glucose adsorption. The findings were supported by molecular docking studies. Heptadecanoic acid and dodecanoic acid were identified as potential compounds with hypoglycemic properties through molecular docking. The extracts were also assessed for their antioxidant activity using DPPH, ABTS, and FRAP assays. The ethyl acetate extracts of C. comosum root and leaf extracts were also able to scavenge DPPH radicals with IC50 values of 108.37±0.06 and 181.79±0.09 µM and ABTS radicals with IC50 values of 126.24±0.13 and 264.409±0.08 µM,respectively. The root and leaf extracts also reduced the ferricyanide complex to ferrocyanide with higher reducing powers of 2.24±0.02 and 1.65±0.03, respectively. The results showed that the ethyl acetate extract of C. comosum root has significant antioxidant and hypoglycemic potential compared to the ethyl acetate extract of C. comosum leaf extract. Thus, it can also be studied to isolate the potential compounds with antihyperglycemic activities.